The shifting of maritime power and the implications for maritime security in Southeast Asia - Ho, Joshua (2009)
The paper discusses how the possession of maritime power can lead to the accrual of economic power and highlights how maritime power is shifting to East Asia by observing trends in the four areas of inter and intra-regional trade flows, regional energy demand, strength of regional merchant fleets and strength of regional navies. The trends in the four areas indicate that maritime power is shifting to East Asia. Correlated to teh increasing maritime power is the increasing economic growth of the region which is expected to surpass that of the United States and the European Union combined in 2015. However, the shift in the economic centre of gravity to East Asia or the Asia-Pacific is by non means a fait accompli and regional stability is critical to the continued economic growth in the region. Consequently, the ability of regional and extra-regional powers, like the United States to manage the power politics that emerge will be a key determinant of regional stability. Specifically, the main maritime challenges to regional stability will be to keep the vital sea lanes secure and to prevent inter-state maritime conflict from arising out of traditional rivalries, from resource competition, of from competing territorial boundary claims. The paper concludes that for long term stability in the region to occur, it would be necessary to nurture the fledgling multilateral institutions to maturity and to move towards greater political, economic and military cooperation and perhaps integration in the future.